Public narrative and sustained civic engagement: The Wichita County Water Conservation Area in Rural Kansas. Issue 2 (15th March 2022) - Lauer, Stephen; Sanderson, Matthew R.
ABSTRACT: Sustained civic engagement is important to the success of social movements, which contribute to community development outcomes. Our qualitative case study of the Wichita County Water Conservation Area (WCA) suggests that sustained civic engagement among producers in Western Kansas can be understood as a positive feedback loop whereby organizers use public narrative to increase social, cultural, and political capitals in their community. The Wichita County WCA team uses public narrative to increase interpersonal solidarity (social capital) and develop a shared sense of meaning and purpose (cultural capital), while taking a diffuse and relational approach to leadership (political capital). They manage emotions such as fear, grief, despair, and frustration in a manner consistent with the Public Narrative model of social action. Our findings suggest that organizers should consider using a public narrative approach to sustain civic engagement in rural communities.